The Relationship between Nutritional Status, Emotional Intelligence, and Age on Basic Locomotor Movements in Early Childhood - Sesi Melati; Sulaiman Sulaiman; Tri Rustiadi (JUARA : Jurnal Olahraga, 2022)
This study was 1) to analyze and determine the relationship between nutritional status and basic locomotor movements in early childhood. 2) Analyzing and knowing the relationship between emotional intelligence and basic locomotor movements in children. 3) Analyzing and knowing the relationship between age and basic locomotor movements in children. 4) Analyzing and knowing the relationship between nutritional status, emotional intelligence and age on basic locomotor movements in early childhood. This study uses a quantitative method with a correlation design. The population in this study is kindergarten children in District XIII Koto Kampar. The sampling technique used purposive sampling consisting of 180 children. The results of this study: 1) There is a relationship between nutritional status and basic locomotor movements. 2) There is a relationship between emotional intelligence and basic locomotor movements. 3) There is a Relationship between Nutritional Status and Basic Locomotor Movements. 4) There is a relationship between nutritional status, emotional intelligence, and age on basic locomotor movements. Based on the results of the study, it can be concluded that there is a significant relationship between nutritional status, emotional intelligence, and age on basic locomotor movements in early childhood, based on simultaneous regression tests. This means that the higher the nutritional status, emotional intelligence, and age of the child, the more active the child's basic locomotor movements are.